TECHNIQUE FOR CONTRAST DETERMINATION IN CASE OF HARMONIC SPATIAL MODULATION OF ILLUMINATION - BOROVYTSKY, VOLODYMYR; HUDZ, OLEKSII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper proposes a method for calculation of the contrast, bias and current phase of harmonic spatial modulation of illumination, which can be used for three-dimensional digital image capture in optical microscopy and other optical-electronic systems. This technique is based on analytical solution of the system of linear equations and allows the calculation of the contrast of harmonic spatial modulation with any values of phase angles. The input data for demodulation is three spatial signals after harmonic modulation with different initial phases as a stack of digital images with harmonic spatial modulation. This data makes it possible to compose the three-dimensional images by the selection of the maximal values of the contrast in three-dimensional space. The paper contains the analytical solution of the system with three linear equations that helps to identify the principal parameters of harmonic spatial modulation, including its average value and contrast. As a result, the expression for contrast calculation is present in an analytical form. This expression is valid for any modulation phase angles that do not coincide.  The proposed technique allows calculation of the contrast for each signal value without any approximation. As a result, the accurate contrast value can be obtained and used for automatic restoration of three-dimensional images.  The advantage of the proposed method is that it can be implemented with economical units that form harmonic spatial modulation of illumination. These units may be installed on most optical microscopes and other electro-optical systems for automatic capture of the three-dimensional images. As a result, the proposed technique significantly reduces the price of transforming economical optical instruments into automatic electro-optical systems for three-dimensional digital image capture.
Keywords: digital image processing; three-dimensional digital image; spatial modulation of illumination; digital demodulation